Persepsi Pegawai Terhadap Kesesuaian Kompensasi, Rotasi Pekerjaan Dan Kepuasan Kerja Terhadap Komitmen Organisasi Serta kinerja Pegawai - Siwy, Herman R.L. (Universitas Sam Ratulangi, 2017)
A source of human resources in this case employees are one of the most important element in an organization either in the sphere of government as well as private which moves in the service sector and non services .A source of human resources this includes a whole by individuals engaged in the activities of the organization starting from its highest level until the lowest involved in operational activities organization. The research found conformity compensation where it has some positive effects significantly to the organization on employees, rotation work influential not significantly to the organization on employees, job satisfaction it has some positive effects significantly to the organization on employees, the organization it has some positive effects significantly to the employee performanceKeywords: Perception employees, compensation, rotation work, satisfaction work, commitment organization, performance employees, papua province